Penerapan Model Problem Based Learning (PBL) pada Pembelajaran Pidato Secara Daring untuk Meningkatkan Kemampuan Berbicara Siswa Sekolah Dasar di Kabupaten Wajo - Aco Aco; Muhammad Dahlan (Departement of Mathematics Education, 2023)
This study aims to determine the application of the problem based learning model to online speech learning to improve elementary school students' speaking skills. The research design is a quantitative description. The type of research used is Classroom Action Research. The procedures in the research are plan (planning), do (implementation), and see (reflection) and are carried out in several cycles until the expected improvement is achieved. Based on the results of the study, namely the problem based learning method is very effective for improving speaking skills through online speech learning. For this reason, it can be concluded that there is an increase in the value of the readiness aspect of pre-action learning (10.15), cycle 1 (15.00), and cycle 2 (16.10), there is an increase in the value of the clarity aspect of pre-action learning (10, 10), cycle 1 (15.20), and cycle 2 (15.20), there was an increase in the value of the content aspects of speech from pre-action learning (10.20), cycle 1 (15.25), and cycle 2 (15, 30). ), cycle 1 (15.70), and cycle 2 (16.56).